Implementing temporally coherent clustering on student activity to predict exam performance & optimizing the learning pathway through markov chain analysis - Anough, Ahmed Saquif Alam; Hossain, Md. Tahmid; Karim, Kazi Ruzlan; Faruk, Umar (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.